2008
DOI: 10.1519/jsc.0b013e31817b03a1
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Outputs During Dynamic Bench Press Under Stable Versus Unstable Conditions

Abstract: Previous studies have suggested that resistance training exercise under unstable conditions decreases the isometric force output, yet little is known about its influence on muscular outputs during dynamic movement. The objective of this study was to investigate the effect of an unstable condition on power, force, and velocity outputs during the bench press. Twenty male collegiate athletes (mean age, 21.3 +/- 1.5 years; mean height, 167.7 +/- 7.7 cm; mean weight, 75.9 +/- 17.5 kg) participated in this study. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 10 publications
1
30
2
8
Order By: Relevance
“…20,24 Yet, minor deficits in force, power, and velocity (6% to 10%) occurred with a dynamic bench press performed on a physioball. 38 Less significant reductions in force with Swiss ball chest press exercises may be attributed to the compression or flattening of the ball, with higher resistance contributing to a more stable platform. 7,9,10 …”
Section: Effect Of Irt On Functional Performancementioning
confidence: 99%
“…20,24 Yet, minor deficits in force, power, and velocity (6% to 10%) occurred with a dynamic bench press performed on a physioball. 38 Less significant reductions in force with Swiss ball chest press exercises may be attributed to the compression or flattening of the ball, with higher resistance contributing to a more stable platform. 7,9,10 …”
Section: Effect Of Irt On Functional Performancementioning
confidence: 99%
“…A number of studies have documented that lower forces are produced when performing resistance activities under unstable conditions. Instability resistance training has been reported to decrease upper-(1,20) and lower-body force output (2,6,14,25) and upper- (19,20) and lower-body muscular power output (14). If strength adaptations are related to the resistance intensity (33,34), then how could instability resistance training with its lower loads still achieve similar strength results?…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, instability resistance training has been reported to decrease upper-and lower-body force output (1,4,6,25), dynamic bench press force, power and velocity (20), muscular power when utilizing an unstable pendulumlike device (19), peak concentric power and force, peak eccentric power and velocity, and range of motion (ROM) during a squat (14). Overload tension on the muscle is essential for fostering strength training adaptations (5,34).…”
Section: Introductionmentioning
confidence: 99%
“…11 In a separate study, performing a bench press on an unstable surface was shown to have no effect on electromyographic (EMG) recordings, although, force output was decreased. 2,13 In contrast, trunk muscle activity increased when performing a squat on an unstable surface. 1 From these findings, the influence of surface stability on muscle activity appears to be muscle and exercise dependent.…”
Section: Exercises Proceduresmentioning
confidence: 99%